PENGEMBANGAN BAHAN AJAR E-BOOK UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS MAHASISWA - Purba, Glory Indira Diana; Hia, Yasifati; Samosir, Katrina (JS (JURNAL SEKOLAH), 2023)
Abstract: Currently, students are expected to be able to keep up with technological advances, especially in the field of education, for this reason they must be able to learn from anywhere, both with online and offline learning systems. In this research, interactive teaching materials will be developed that can train students' mathematical reasoning abilities. The interactive teaching materials that will be developed are in the form of e-books that use the Problem Based Learning (PBL) model syntax. The aim of this research is to see the validity, practicality and effectiveness of teaching materials in the form of electronic books in improving the mathematical reasoning abilities of students majoring in mathematics education at Medan State University. After testing, a validity value of 4.7 was obtained for the media and 4.8 for the material developed, where this value was in the very feasible range. From the results of the student response questionnaire, a practicality score of 85.8% was obtained, where this category was within the practical category range. The effectiveness aspect is achieved if 75% of the formulated learning objectives can be achieved by 65% of students. Based on the completion score, there were 26 students who had completed individually or 86.6%.Keywords: PBL Model, e-book teaching materials, mathematical reasoning abilitiesAbstrak: Pada saat ini peserta didik diharapkan mampu mengikuti kemajuan teknologi terutama dalam bidang pendidikan, untuk itu mereka harus dapat belajar dari mana saja baik dengan sistem pembelajaran online maupun offline. Dalam penelitian ini akan dikembangkan bahan ajar interaktif yang dapat melatih kemampuan penalaran matematis siswa. Bahan ajar interaktif yang akan dikembangkan berupa e-book yang menggunakan sintaks model Problem Based Learning (PBL). Adapun tujuan dari penelitian ini yaitu untuk melihat kevalidan, kepraktisan dan keefektifan dari bahan ajar yang berbentuk buku elektronik dalam meningkatkan kemampuan penalaran matematis mahasiswa jurusan pendidikan matematika Universitas Negeri Medan. Setelah dilakukan ujicoba maka diperoleh nilai kevalidan sebesar 4,7 untuk media dan 4,8 untuk materi yang dikembangkan, Dimana nilai tersebut ada dalam rentang sangat layak. Dari hasil angket respon mahasiswa diperoleh nilai kepraktisan sebesar 85,8% dimana kategori tersebut berada dalam rentang kategori praktis. Untuk aspek keefektifan tercapai apabila 75% tujuan pembelajaran yang dirumuskan dapat dicapai oleh 65% siswa. Berdasarkan nilai ketuntasan, ada 26 orang mahasiswa yang telah tuntas secara individual atau sebesar 86,6%.Kata kunci: Model PBL, Bahan Ajar, e-book, Kemampuan Penalaran Matematis.